Remarkable biodiversity of flabelligerids in Japan: seven new species of Diplocirrus (Annelida: Flabelligeridae) from Japanese waters - Jimi, Naoto; Fujiwara, Yoshihiro; Kajihara, Hiroshi (Zootaxa, 2017)
Seven new species of Diplocirrus are described from Japan: D. asamushiensis sp. nov., D. imajimai sp. nov., D. mamoi sp. nov., D. ohtsukai sp. nov., D. seisuiae sp. nov., D. tohokuensis sp. nov., and D. toyoshioae sp. nov. These species are distinguished from all the known species of Diplocirrus by the following features: length of the cephalic cage, length of lateral papillae, presence of gonopodial lobe, adhering pattern of sediment particles, length of caruncle, length and morphological feature of branchiae, articles and morphological features of neurochaetae, and swollen area along the body.